ASSOCIATING LIVER PARTITION AND PORTAL VEIN LIGATION (ALPPS) FOR COLORECTAL LIVER METASTASIS: REVIEW & SINGLE-CENTER STUDY - Ruivo, Ana (2022)
The associating liver partitioning and portal vein ligation for staged hepatectomy has gained interest in the treatment of unresectable colorectal liver metastases as it has allowed to expand the limits of oncological resectability. Despite the initial poor outcomes associated to this procedure, recent reports have showed reduced morbimortality in well selected patients. The current study evaluates the outcomes of ALPPS procedure in treatment of colorectal liver metastasis at our department and identify morbimortality and survival prognostic factors. A retrospective cohort study was performed, all consecutive patients submitted to ALPPS procedure between 2015 and 2020 were included. Twenty-one patients with 61,8±10,8 (37-78), 76,2% were male, with 12,05±6,34 (5-30) hepatic nodules, whose largest size was 42.3 ± 17, 5 (18-75) mm. Among these, 71.4% underwent induction chemotherapy with FOLFIRI and 61,9% with plus Cetuximab, mean of 10,9±5,6 (4-24) cycles. At ALPPS stage 1, 6±4 (1-18) nodules were resected, 19% with concomitant splenic artery occlusion and a mean Pringle Maneuver of 33±26 (0-94) minutes. All patients did adjuvant CT. We report a global mortality of 9,6% and a major morbidity (MMb) of 28,6%. The multivariable analysis identified as risk factor for MMb: more than 10 nodules, size>38mm, interstage interval> 14 days and the resection of more than 4 lesions at stage 1. The overall survival and disease-free survival rates were 25,9± 4,2 (17,6- 34,1), 17,64 ±3,95 (9,9-25,4) moths, respectively. Age >56 years and size >38mm were identified as risk factor for poor outcome. More than 10 cycles of neoadjuvant chemotherapy were identified as risk factor for poor outcome at 2 years. Our results are similar to the recently established reference values.